FRI0627 Ultrasound hand examination is more sensitive in diagnosing hand osteoarthritis than conventional radiography: comparison between different ultrasonographic scores. (15th June 2017) - Hussain, S; Sivakumaran, P; Ciurtin, C
Abstract : Background: Hand osteoarthritis (OA) diagnosis is based on a combination of clinical, imaging features and assessment of risk factors, together with clinical associations and outcomes (1). In a real-life context, clinicians face difficulty in differentiating between OA and other hand arthropathies, particularly when the clinical examination is equivocal (e.g. no obvious bony enlargement with the characteristic distribution for hand OA). Objectives: This is the first study to investigate the usefulness of a standardised ultrasound (US) examination protocol for hand joints in diagnosing hand osteoarthritis (OA) and the correlations between several US scores and clinical, inflammatory and radiographic parameters, aiming to explore which type of investigations are the most useful for diagnosing hand OA. Methods: We conducted a cross-sectional study including 62 patients, ultimately diagnosed with hand OA based on the ACR diagnosis criteria (2). We compared the 34 joint score of the hand, with smaller, pre-defined joint scores including two scores of 22 and 12 joint each, and another 10 and 6 joint scores for OA. We correlated the US findings with radiographic scores (2108 joints). Results: Radiographic osteophyte scores correlated very well with the predefined US scores detailed above (R=0.381 to 0.645, P<0.05), despite having a low sensitivity for detection of osteophytes (58.6%), and an even lower sensitivity for detection of erosions (38.4%) when compared with the 34 joint US score. There was a good correlation between different US scores (R =0.53 to 0.97, P<0.05), apart from the 6 joint score excluding the proximal interphalangeal joints (R= -0181 to 0.207, P>0.05). Conclusions: US examination of the hands can facilitate the diagnosis of hand OA in patients who do not fulfil the ACR criteria, by identifying the presence of osteophytes with the particular distribution and number required for diagnosis in a proportion of patients that was three times higher than that of patients diagnosed based on clinical examination and hand radiography alone. References: Zhang W, Doherty M, Leeb BF, Alekseeva L, Arden NK, Bijlsma JW, et al. EULAR evidence-based recommendations for the diagnosis of hand osteoarthritis: report of a task force of ESCISIT. Annals of the rheumatic diseases. 2009 Jan;68(1):8–17. PubMed PMID: 18250111. Epub 2008/02/06. eng. Altman R, Alarcon G, Appelrouth D, Bloch D, Borenstein D, Brandt K, et al. The American College of Rheumatology criteria for the classification and reporting of osteoarthritis of the hand. Arthritis and rheumatism. 1990 Nov;33(11):1601–10. PubMed PMID: 2242058. Epub 1990/11/01. eng. Acknowledgements: S. Hussain and P. Sivakumaran contributed equally to this study. Disclosure of Interest: None declared